(untitled) - Yusuf, Shahid (Washington, DC 20433, 2008)
China Urbanizes: Consequences, Strategies, and Policies identify the key developments to watch and discuss the policies that would affect the course as well as the fruitfulness of change. The key challenges facing China in the next two decades derive from the ongoing process of urbanization. China's urbanization rate in 2005 was about 43%. Over the next 10-15 years, China s urbanization rate is expected to rise to well over 50% adding an additional 200 million mainly rural migrants to the current urban population of 560 million. How China copes with such a large migration flow will strongly influence rural-urban inequality, the pace at which urban centers expand their economic performance, and the urban environment. The growing population will necessitate a big push strategy to maintain high rate of investment in housing and the urban physical infrastructure and urban services. To finance such expansion will require a significant strengthening and diversification of China s financial system. Growing cities will greatly increase consumption of energy and water. Containing this without at the same time constraining the economic performance of cities or the improvement in the standards of living will call for enlightened policies, strategies, careful urban planning, and significant technological advances.
Keywords: Quy hoạch thành phố,Đô thị hóa,Trung Quốc,City planning,Urbanization,Trung Quốc; Trung Quốc,Trung Quốc,Dân số,Điều kiện kinh tế; China,China